Acetone gas-sensitive material, preparation method thereof and application of acetone gas-sensitive material in acetone gas sensor
Through the synergistic effects of the p-p heterojunction structure of YbFeO3-BiFeO3 composite material and the Fe2+/Fe3+ redox pair, the problems of low sensitivity and high operating temperature of the existing acetone gas sensor are solved, and acetone gas with high sensitivity and low detection lower limit is achieved Testing, suitable for diabetes diagnosis.
Patent Information
- Application Number
- CN202310807573.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-03
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-07-03
AI Technical Summary
The existing acetone gas sensors based on binary metal oxide materials have problems such as low sensitivity, high detection limit and high operating temperature, especially in diabetes diagnosis, it is difficult to effectively detect low concentrations of acetone gas.
Using YbFeO3-BiFeO3 composite material, the gas-sensitive performance is improved by forming p-p heterojunction, and the Fe2+/Fe3+ redox pair and oxygen adsorption process enhances the response to acetone, reduces the working temperature, and uses simple solid-phase sintering and acid etching. The corrosion preparation method significantly improves the detection lower limit and sensitivity.
High sensitivity detection of acetone gas is achieved, the working temperature is reduced, and the response strength and selectivity of the sensor are significantly improved. The lower detection limit reaches 25ppb, the working temperature is reduced to ≤200℃, and the response level reaches 32.6@10ppm.
Smart Images

Figure CN119246623A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a YbFeO3-BiFeO3 composite sensitive material and a preparation method thereof and application in an acetone gas sensor, belonging to the technical field of semiconductor metal oxide gas sensors. Background Art
[0002] With the development of medicine, breath biomarker detection has become a promising non-invasive disease diagnosis technology. As a breath biomarker for diabetes, acetone detection provides a simple, effective and non-invasive method for early diagnosis of diabetes. The acetone concentration in the breath of healthy people is less than 0.9ppm, while the acetone concentration in diabetic patients is higher than 1.8ppm. Therefore, the development of a highly sensitive, low detection limit acetone gas sensor is crucial for the prevention and diagnosis of diabetes.
[0003] At present, researchers have successively developed acetone gas sensors based on binary metal oxides such as SnO2, WO3, ZnO, Fe2O3, Co3O4, CuO, NiO, etc., but they still face the challenges of low sensitivity, high detection limit and especially high operating temperature, which hinders their application in diabetes diagnosis. Although perovskite-type ternary oxides ABO3 (such as BiFeO3) show unique advantages in gas-sensitive materials due to their highly adjustable structure and chemical composition, non-stoichiometric stability after doping, etc., the existing perovskite-type ternary oxides (such as BiFeO3) have low acetone gas sensing performance and still face challenges in the application of detecting low-concentration acetone gas. Summary of the invention
[0004] To this end, the present invention provides an acetone gas-sensitive material and a preparation method thereof, and application of an acetone gas sensor based on a YbFeO3-BiFeO3 composite sensitive material.
[0005] On the one hand, the present invention provides an acetone gas-sensitive material, characterized in that the composition of the acetone gas-sensitive material is a YbFeO3-BiFeO3 composite material, and a pp heterojunction is formed between YbFeO3 and BiFeO3.
[0006] In the present invention, two gas-sensitive materials are composited to form a heterogeneous structure, and the synergistic effect of the two can be used to further improve the gas-sensitive performance, thereby obtaining a high-performance acetone gas sensor.
[0007] The specific working principle is: when the YbFeO3-BiFeO3 sensor is exposed to air, oxygen molecules are adsorbed on the surface and converted into adsorbed oxygen ions (O2 - , O - , O 2-). Therefore, the hole concentration on the surface increases, resulting in a decrease in resistance. When the sensor is exposed to acetone gas, the acetone molecules undergo a redox reaction with the oxygen ions, and the electrons are released back into the composite material. At this time, the electrons recombine with the holes, causing the hole concentration to decrease, resulting in an increase in resistance. By measuring the change in resistance before and after the sensor comes into contact with acetone gas, the purpose of detecting acetone is achieved. The responsivity of the acetone sensor is defined as the resistance R of the sensor in acetone. g and the air resistance R a ratio.
[0008] Compared with BiFeO3, YbFeO3-BiFeO3 composites have a higher 2+ / Fe 3+ The increase in redox pairs improves the response intensity to acetone gas. On the one hand, since the band gap of YbFeO3 (1.7eV) is smaller than that of BiFeO3, electrons will transfer from BiFeO3 to YbFeO3, and holes will transfer from YbFeO3 to BiFeO3, and the energy band at the heterojunction will bend until the Fermi level reaches equilibrium. The formation of the heterojunction can promote interfacial electron transfer and interfacial reaction, and enhance the adsorption of surface oxygen, thereby improving gas-sensitive performance. On the other hand, the YbFeO3-BiFeO3 composite material prepared based on this method has more Fe 2+ / Fe 3+ Redox couple. During oxygen adsorption, Fe 2+ Oxidized to Fe 3+ , releasing electrons to provide adsorbed oxygen, which promotes the large-scale adsorption of oxygen ions. After reacting with acetone, electrons are released into the composite material, promoting Fe 3+ Reduced to Fe 2+ Therefore, Fe 2+ / Fe 3+ The increase in concentration also promoted the response of YbFeO3-BiFeO3 composites to acetone.
[0009] Preferably, the content of YbFeO3 in the YbFeO3-BiFeO3 composite material is 1 to 25 wt.%, preferably 5 to 20 wt.%, more preferably 6 to 16 wt.%, and most preferably 10 to 14 wt.%.
[0010] Preferably, the particle size of the YbFeO3-BiFeO3 composite material is 0.2 to 5 μm, preferably 0.2 to 1 μm.
[0011] In a second aspect, the present invention provides a method for preparing an acetone gas-sensitive material, comprising: 1) Mix Yb2O3 powder and BiFeO3 powder, and calcine at 650-750°C for 3-5h to obtain calcined powder; 2) The obtained calcined powder is placed in a nitric acid solution and stirred, and then washed and dried to obtain the YbFeO3-BiFeO3 composite material.
[0012] Preferably, the mass of the Yb2O3 powder is 1 to 15 wt.% of the mass of the BiFeO3 powder; The concentration of the nitric acid solution is 1 to 3 mol / L; The stirring process is performed at a rotation speed of 600 to 800 rpm and for a time of 0.5 to 2 hours.
[0013] In a third aspect, the present invention provides an acetone gas sensor based on a YbFeO3-BiFeO3 composite material, characterized in that it comprises: a YbFeO3-BiFeO3 sensitive film prepared from the above-mentioned acetone gas sensitive material.
[0014] Preferably, an acetone gas sensor based on a YbFeO3-BiFeO3 composite material comprises: a substrate, interdigital electrodes and a YbFeO3-BiFeO3 sensitive film formed on one surface of the substrate, and a heating electrode formed on the other surface of the substrate.
[0015] Preferably, the thickness of the YbFeO3-BiFeO3 sensitive film is 40-80 μm.
[0016] Preferably, the interdigital electrodes are made of Au, Cr or Ag-Pd. Preferably, the heating electrodes are made of Pt, Cu or Ni-Cr. Preferably, the substrate is made of Al2O3 or Si.
[0017] Preferably, in the detection of acetone gas, the optimal operating temperature of the acetone gas sensor based on the YbFeO3-BiFeO3 composite material is ≤200°C, and the response to 10 ppm acetone at the optimal operating temperature is as high as 32.6.
[0018] In another aspect, the present invention provides a method for preparing an acetone gas sensor based on a YbFeO3-BiFeO3 composite material, wherein the method for preparing the YbFeO3-BiFeO3 sensitive film comprises: (1) dispersing the YbFeO3-BiFeO3 composite material in an organic solvent to obtain a slurry; (2) The obtained slurry is coated on the surface of the interdigital electrode, and then dried and aged to obtain a YbFeO3-BiFeO3 sensitive film.
[0019] Preferably, the ratio of the YbFeO3-BiFeO3 composite material to the organic solvent is (10-20) mg: (15-30) μL; preferably, the organic solvent is at least one of pineneol, ethanol, acetone and glycerol.
[0020] Preferably, the coating method is screen printing; The drying temperature is 200-300°C and the drying time is 4-12h; The temperature of the aging treatment is 200-300° C., and the time is 24-48 hours.
[0021] Beneficial effects: 1. The present invention successfully prepares the YbFeO3-BiFeO3 composite material by simple solid phase sintering combined with acid etching, and the preparation method is simple and low in cost; 2. The present invention significantly reduces the detection limit of BiFeO3-based sensors (theoretically calculated to be 25 ppb) by compounding a small amount of YbFeO3 with BiFeO3, and improves the sensitivity (S = 7 @ 400 ppb; S = 32.6 @ 10 ppm Figure 5 As shown in the figure), the operating temperature is greatly reduced (≤200°C); in addition, the sensor has good stability and selectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a schematic diagram of the structure of the acetone gas sensor of the present invention; in the figure, 1-YbFeO3-BiFeO3 sensitive film; 2-interdigital electrodes; 3-substrate; 4-heating electrode; Figure 2 The X-ray diffraction spectrum of the YbFeO3-BiFeO3 composite material prepared in Example 1; Figure 3 It is a comparison chart of the response values of the BiFeO3 sensor in Comparative Example 1 and the YbFeO3-BiFeO3 sensor prepared in Example 1 to 10 ppm acetone gas at 160-300°C; Figure 4 The response and recovery curves of the BiFeO3 sensor in Comparative Example 1 and the YbFeO3-BiFeO3 sensor prepared in Example 1 to different concentrations of acetone at the optimal working temperature and the response value comparison diagram; Figure 5 The response and recovery curves and response values of the YbFeO3-BiFeO3 sensor prepared in Example 1 to different concentrations of acetone at different temperatures; Figure 6 The response of the YbFeO3-BiFeO3 sensor prepared in Example 1 to different reducing gases; Figure 7 To compare the response and recovery curves of YbFeO3-BiFeO3 sensors prepared with different Yb2O3 doping amounts to 10ppm acetone at 220℃ and the changes of response with Yb2O3 doping amount; Figure 8This is the response and recovery curve of the YbFeO3-BiFeO3 sensor prepared in Example 5 to 10 ppm acetone at an operating temperature of 220°C; as can be seen from the figure, the response of the YbFeO3-BiFeO3 sensor to 10 ppm acetone can reach 30.3. DETAILED DESCRIPTION
[0023] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.
[0024] In the present disclosure, an acetone gas sensor based on a YbFeO3-BiFeO3 composite material is described. Figure 1 As shown, it includes: a gas-sensitive film based on a YbFeO3-BiFeO3 composite material, an interdigital electrode, a substrate, and a heating electrode.
[0025] In the present invention, a small amount of Yb2O3 and BiFeO3 powders are uniformly mixed, and then subjected to high temperature roasting and acid corrosion to obtain a pure phase YbFeO3-BiFeO3 composite material. An appropriate amount of the above composite material is mixed with pine alcohol, and after uniform grinding, a slurry with moderate viscosity is obtained, which is screen-printed on a substrate with interdigital electrodes and a heating electrode, and heated and aged to obtain an acetone gas sensor based on the YbFeO3-BiFeO3 composite material. The following is an exemplary description of the preparation method of an acetone gas sensor based on a YbFeO3-BiFeO3 composite material.
[0026] Preparation of BiFeO3 powder material. In the present invention, BiFeO3 powder is prepared by hydrothermal method, sol-gel method, solid phase reaction method, electrospinning method, etc., and it is only necessary to ensure that BiFeO3 is a rhombohedral crystal phase with an average size of less than 3 μm (preferably, 0.1 to 2 μm, more preferably 0.1 to 1 μm).
[0027] As an example of using a hydrothermal method to prepare BiFeO3 powder, it includes: adding ferric nitrate nonahydrate and bismuth nitrate pentahydrate to a dilute nitric acid solution, stirring continuously until all are dissolved, and obtaining a mixed solution. Then adding a certain concentration of potassium hydroxide solution to adjust the pH and react, and the obtained reaction product is centrifuged and washed; the reaction product is added to an aqueous solution containing potassium hydroxide and potassium nitrate, stirred evenly, and transferred to a hydrothermal kettle for heating reaction, and the initial bismuth ferrite powder is obtained after centrifugation, washing, and drying.
[0028] In an optional embodiment, the concentrations of ferric nitrate nonahydrate and bismuth nitrate pentahydrate in the mixed solution may be 12 to 18 mmol, respectively. The volume of the dilute nitric acid solution is 100 mL, and the concentration is 1 to 3 mol / L. The concentration of the potassium hydroxide solution may be 10 to 12 mol / L, so that the pH of the mixed solution is 8 to 14. The concentration of potassium hydroxide in the aqueous solution containing potassium hydroxide and potassium nitrate is 10 to 12 mol / L, and the concentration of potassium nitrate is 2.2 to 2.8 mol / L. The hydrothermal time may be 20 to 48 h, and the hydrothermal temperature may be 180 to 220°C.
[0029] Take a small amount of Yb2O3 and BiFeO3 powders and mix them evenly, then calcine at high temperature and acid etch to obtain a pure phase YbFeO3-BiFeO3 composite material. The raw material content of Yb2O3 is 1wt.%~15wt.%, preferably 5wt.~10wt.%, and more preferably 10wt.%; the calcination temperature is 650~750℃, and the sintering time is 3~5h. The purpose of calcination is to form a YbFeO3-BiFeO3 composite material. The nitric acid concentration is 1~3mol / L, the stirring time is 0.5~2h, and the acid etch purpose is to remove Bi 12 (Bi 0.5 Fe 0.5 ) 19.5 impurities and at the same time expose the Fe active sites and increase the surface adsorbed oxygen, thereby enhancing the gas sensing performance.
[0030] An appropriate amount of YbFeO3-BiFeO3 composite material was mixed with pinene alcohol, and then uniformly ground to obtain a slurry with moderate viscosity, which was screen-printed on a substrate with interdigital electrodes and a heating electrode, and then heated to remove the pinene alcohol. After aging treatment, an acetone gas sensor based on the YbFeO3-BiFeO3 composite material was obtained. The heating temperature was 200-300℃ for 4-12h; the aging temperature was 200-300℃ for 24-48h.
[0031] The YbFeO3-BiFeO3 acetone gas sensor was placed in a dynamic gas-sensitive test system, and acetone gas of different concentrations was detected by measuring its resistance change.
[0032] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0033] Example 1 Acetone gas sensor based on YbFeO3-BiFeO3 composite material and preparation method thereof, the specific method is as follows: (1) Weigh ferric nitrate nonahydrate and bismuth nitrate pentahydrate in a molar ratio of 1:1, add them to a 2 mol / L dilute nitric acid solution, and stir continuously until they are completely dissolved; (2) adding 12 mol / L potassium hydroxide to react, adjusting the pH of the solution to 14, and centrifuging and washing the obtained reaction product; (3) adding the reaction product prepared in step (2) to an aqueous solution of 12 mol / L potassium hydroxide and 2 mol / L potassium nitrate, stirring evenly and transferring to a hydrothermal kettle for reaction, the hydrothermal time is 24 h, and the hydrothermal temperature is 180° C. After centrifugation, washing, and drying, BiFeO3 powder is obtained; (4) 10 wt.% Yb2O3 and BiFeO3 powders were uniformly mixed, and then calcined at 700°C for 4 hours; the resulting composite material was placed in a 2 mol / L HNO3 solution and stirred evenly with a magnetic stirrer; the above powders were washed several times with deionized water and anhydrous ethanol, and then dried at 70°C for 24 hours to obtain a pure phase YbFeO3-BiFeO3 composite material; the content of YbFeO3 in the YbFeO3-BiFeO3 composite material was 13.4 wt.%; (5) 10 mg of YbFeO3-BiFeO3 powder was mixed with 20 μL of pinene alcohol, and the mixture was uniformly ground to obtain a slurry with moderate viscosity, which was then coated on the side of the Al2O3 ceramic sheet with Au interdigital electrodes using screen printing technology. The film thickness was 60 μm. (6) placing the sensitive film prepared in step (5) in an oven and drying at 250° C. for 6 h, and then soldering the pins of the sensor to the device base; (7) The sensor prepared in step (6) is placed in a dynamic gas-sensitive test system for aging treatment at a temperature of 250° C. for 24 h to obtain a YbFeO3-BiFeO3 acetone gas sensor.
[0034] Figure 2 This is the X-ray diffraction spectrum of the YbFeO3-BiFeO3 composite material prepared in Example 1. It can be seen from the figure that only YbFeO3 and BiFeO3 exist in the YbFeO3-BiFeO3 composite material, and there is no other impurity phase.
[0035] Figure 3The response of the YbFeO3-BiFeO3 sensor in Example 1 to 10 ppm acetone gas at 160-300°C is 16.6 times higher than that of the BiFeO3 sensor, and the optimal operating temperature is reduced from 280°C to 200°C, indicating that the introduction of YbFeO3 and the formation of a pp heterojunction with BiFeO3 greatly improve the gas-sensitive response to acetone and reduce the operating temperature.
[0036] Figure 4 The response and recovery curves of the YbFeO3-BiFeO3 sensor in Example 1 to different concentrations of acetone at the optimal operating temperature and the change of the response with the acetone concentration are shown. It can be seen from the figure that with the increase of the acetone gas concentration, the response value of the YbFeO3-BiFeO3 sensor increases rapidly, and in the acetone concentration ranges of 0.4-1ppm and 2-10ppm, respectively, the response and acetone concentration show a good linear growth relationship.
[0037] Figure 5 The response and recovery curves of the YbFeO3-BiFeO3 sensor prepared in Example 1 to different concentrations of acetone at different temperatures, as well as the change of the response with the acetone concentration; it can be seen from the figure that the optimal operating temperature of the YbFeO3-BiFeO3 sensor for low concentration acetone can be as low as 160°C, at which time the response to 400ppb acetone can reach 7; the detection limit of the sensor is relatively low, and the theoretical calculated value reaches 25ppb.
[0038] Figure 6 This is the response of the YbFeO3-BiFeO3 sensor prepared in Example 1 to different reducing gases. It can be seen from the figure that the example sensor has good selectivity for acetone gas.
[0039] Figure 7 In order to compare the response and recovery curves of YbFeO3-BiFeO3 sensors prepared with different Yb2O3 doping amounts to 10ppm acetone at an operating temperature of 220℃, as well as the change of response with Yb2O3 doping, it can be seen from the figure that the responsiveness of the sensor increases approximately linearly with the increase of Yb2O3 doping, and the highest value of 31.1 is obtained when the Yb2O3 doping amount is 10wt.%; when the Yb2O3 doping amount is further increased to 15wt.%, the responsiveness decreases due to the appearance of impurities.
[0040] Example 2 Acetone gas sensor based on YbFeO3-BiFeO3 composite material and preparation method thereof, the specific method is as follows: (1) Weigh ferric nitrate nonahydrate and bismuth nitrate pentahydrate in a molar ratio of 1:1, add them to a 2 mol / L dilute nitric acid solution, stir continuously until all dissolved, and then add 0.75 g of tartaric acid; (2) heating the solution prepared in step (1) at 250° C. until all the water evaporates, and then calcining at 600° C. for 2 h to obtain BiFeO3 powder; (3) 1wt.% Yb2O3 and BiFeO3 powders were uniformly mixed, and then calcined at 700°C for 4h; the obtained composite material was placed in a 2mol / L HNO3 solution and stirred evenly with a magnetic stirrer; the above powders were washed several times with deionized water and anhydrous ethanol, and then dried at 70°C for 24h to obtain a YbFeO3-BiFeO3 composite material; the content of YbFeO3 in the YbFeO3-BiFeO3 composite material was 1.3wt.%; (5) 10 mg of YbFeO3-BiFeO3 powder was mixed with 20 μL of pinene alcohol, and the mixture was uniformly ground to obtain a slurry with moderate viscosity, which was then coated on the side of the Al2O3 ceramic sheet with Au interdigital electrodes using screen printing technology. The film thickness was 60 μm. (6) placing the sensitive film prepared in step (5) in an oven and drying at 250° C. for 6 h, and then soldering the pins of the sensor to the device base; (7) The sensor prepared in step (6) is placed in a dynamic gas-sensitive test system for aging treatment at a temperature of 250° C. for 24 h to obtain a YbFeO3-BiFeO3 acetone gas sensor.
[0041] Example 3 The preparation process of the YbFeO3-BiFeO3 acetone gas sensor in this Example 3 refers to that in Example 1, the difference is that: 3wt.% Yb2O3 and BiFeO3 powders are uniformly mixed, and then calcined at 700°C for 4h; the obtained composite material is placed in a 2mol / L HNO3 solution and stirred evenly with a magnetic stirrer; the above powder is washed several times with deionized water and anhydrous ethanol, and then dried at 70°C for 24h to obtain a pure phase YbFeO3-BiFeO3 composite material; the content of YbFeO3 in the YbFeO3-BiFeO3 composite material is 4.0wt.%.
[0042] Example 4 The preparation process of the YbFeO3-BiFeO3 acetone gas sensor in this Example 4 refers to that in Example 1, the difference is that: 5wt.% Yb2O3 and BiFeO3 powders are uniformly mixed, and then calcined at 700°C for 4h; the obtained composite material is placed in a 2mol / L HNO3 solution and stirred evenly with a magnetic stirrer; the above powder is washed several times with deionized water and anhydrous ethanol, and then dried at 70°C for 24h to obtain a pure phase YbFeO3-BiFeO3 composite material; the content of YbFeO3 in the YbFeO3-BiFeO3 composite material is 6.7wt.%.
[0043] Example 5 The preparation process of the YbFeO3-BiFeO3 acetone gas sensor in this Example 5 refers to that in Example 1, the difference is that: 10wt.% Yb2O3 and BiFeO3 powders are uniformly mixed, and then calcined at 750°C for 4h; the obtained composite material is placed in a 2mol / L HNO3 solution and stirred evenly with a magnetic stirrer; the above powder is washed several times with deionized water and anhydrous ethanol, and then dried at 70°C for 24h to obtain a pure phase YbFeO3-BiFeO3 composite material; the content of YbFeO3 in the YbFeO3-BiFeO3 composite material is 13.4wt.%. Figure 8 This is the response and recovery curve of the YbFeO3-BiFeO3 sensor prepared in Example 5 to 10 ppm acetone at an operating temperature of 220°C; as can be seen from the figure, the response of the YbFeO3-BiFeO3 sensor to 10 ppm acetone can reach 30.3.
[0044] Example 6 The preparation process of the YbFeO3-BiFeO3 acetone gas sensor in this Example 6 refers to that in Example 1, the difference is that: 15wt.% Yb2O3 and BiFeO3 powders are uniformly mixed, and then calcined at 700°C for 4h; the obtained composite material is placed in a 2mol / L HNO3 solution and stirred evenly with a magnetic stirrer; the above powder is washed several times with deionized water and anhydrous ethanol, and then dried at 70°C for 24h to obtain a YbFeO3-BiFeO3 composite material; the content of YbFeO3 in the YbFeO3-BiFeO3 composite material is 20.1wt.%.
[0045] Comparative Example 1 The acetone sensor is prepared using pure BiFeO3 as the sensitive material. The specific process is as follows: (1) Weigh ferric nitrate nonahydrate and bismuth nitrate pentahydrate in a molar ratio of 1:1, add them to a 2 mol / L dilute nitric acid solution, and stir continuously until they are completely dissolved; (2) adding 12 mol / L potassium hydroxide to react, adjusting the pH of the solution to 14, and centrifuging and washing the obtained reaction product; (3) adding the reaction product prepared in step (2) to an aqueous solution of 12 mol / L potassium hydroxide and 2 mol / L potassium nitrate, stirring evenly and transferring to a hydrothermal kettle for reaction, the hydrothermal time is 24 h, and the hydrothermal temperature is 180° C. After centrifugation, washing, and drying, BiFeO3 powder is obtained; (4) 10 mg BiFeO3 powder was mixed with 20 μL pinene alcohol, and the mixture was uniformly ground to obtain a slurry with moderate viscosity, which was then coated on the side of the Al2O3 ceramic sheet with Au interdigital electrodes using screen printing technology. The film thickness was 60 μm. (5) placing the sensitive film prepared in step (4) in an oven and drying it at 250° C. for 6 h, and then soldering the pins of the sensor to the device base; (6) The sensor prepared in step (5) is placed in a dynamic gas-sensitive test system for aging treatment at a temperature of 250° C. for 24 h to obtain an acetone gas sensor based on BiFeO 3 material.
Claims
1. An acetone gas-sensitive material, characterized in that: The acetone gas-sensitive material is composed of a YbFeO3-BiFeO3 composite material, and a pp heterojunction is formed between YbFeO3 and BiFeO3.
2. The acetone gas-sensitive material according to claim 1, characterized in that: The content of YbFeO3 in the YbFeO3-BiFeO3 composite material is 1 to 25 wt.%, preferably 5 to 20 wt.%, more preferably 6 to 16 wt.%, and most preferably 10 to 14 wt.%.
3. The acetone gas-sensitive material according to claim 1 or 2, characterized in that: The particle size of the YbFeO3-BiFeO3 composite material is 0.2-5 μm, preferably 0.2-1 μm.
4. A method for preparing an acetone gas-sensitive material according to any one of claims 1 to 3, characterized in that: include: 1) Mix Yb2O3 powder and BiFeO3 powder, and calcine at 650-750°C for 3-5h to obtain calcined powder; 2) The obtained calcined powder is placed in a nitric acid solution and stirred, and then washed and dried to obtain the YbFeO3-BiFeO3 composite material.
5. The preparation method according to claim 1, characterized in that: The mass of the Yb2O3 powder is 1 to 15 wt.% of the mass of the BiFeO3 powder; The concentration of the nitric acid solution is 1 to 3 mol / L; The stirring process is performed at a rotation speed of 600 to 800 rpm and for a time of 0.5 to 2 hours.
6. An acetone gas sensor based on YbFeO3-BiFeO3 composite material, characterized in that: include: A YbFeO3-BiFeO3 sensitive film prepared from the acetone gas sensitive material according to any one of claims 1 to 3.
7. The acetone gas sensor based on the YbFeO3-BiFeO3 composite material according to claim 6, characterized in that: include: A substrate, an interdigital electrode and a YbFeO3-BiFeO3 sensitive film formed on the surface of one side of the substrate, and a heating electrode formed on the surface of the other side of the substrate.
8. The acetone gas sensor based on the YbFeO3-BiFeO3 composite material according to claim 7, characterized in that: The thickness of the YbFeO3-BiFeO3 sensitive film is 40-80 μm.
9. The acetone gas sensor based on the YbFeO3-BiFeO3 composite material according to claim 7 or 8, characterized in that: The interdigital electrodes are composed of Au, Cr or Ag-Pd; the heating electrodes are composed of Pt, Cu or Ni-Cr; and the substrate is composed of A2O3 or Si.
10. The acetone gas sensor based on the YbFeO3-BiFeO3 composite material according to any one of claims 7 to 9, characterized in that: In the detection of acetone gas, the optimal operating temperature of the acetone gas sensor based on YbFeO3-BiFeO3 composite material is ≤200℃, and the response to 10ppm acetone is as high as 32.6 at the optimal operating temperature.
11. A method for preparing an acetone gas sensor based on a YbFeO3-BiFeO3 composite material as claimed in any one of claims 7 to 10, characterized in that: The preparation method of the YbFeO3-BiFeO3 sensitive film comprises: (1) dispersing the YbFeO3-BiFeO3 composite material in an organic solvent to obtain a slurry; (2) The obtained slurry is coated on the surface of the interdigital electrode, and then dried and aged to obtain a YbFeO3-BiFeO3 sensitive film.
12. The preparation method according to claim 11, characterized in that: The ratio of the YbFeO3-BiFeO3 composite material to the organic solvent is (10-20) mg: (15-30) μL; preferably, the organic solvent is at least one of pineneol, ethanol, acetone and glycerol.
13. The preparation method according to claim 11 or 12, characterized in that: The coating method is screen printing; the drying temperature is 200-300°C and the drying time is 4-12 hours; The temperature of the aging treatment is 200-300° C., and the time is 24-48 hours.
Citation Information
Patent Citations
Acetone air-sensitive material and uses thereof
CN101162211A
Quantum dot film material with gas-sensitive property and application thereof
CN114933758A
Raw material solution for forming film of ferroelectric thin film and formation of film
JP2000119021A
